Geomechanics in Depleted Faulted Reservoirs - Nikolaos Markou; Panos Papanastasiou (Energies, 2020)
This paper examines the impact of the effective stresses that develop during depletion of a faulted reservoir. The study is based on finite element modeling using 2D plane strain deformation analysis with pore pressure and elastoplastic deformation of the reservoir and sealing shale layers governed by the Drucker–Prager plasticity model. The mechanical properties and response of the rock formations were derived from triaxial test data for the sandstone reservoirs and correlation functions for the shale layers. A normal fault model and a reverse fault model were built using seismic data and interpretation of field data. The estimated tectonic in-situ stress field was transformed to the plane of the modeled geometry. Sensitivity studies were performed for uncertainties on the values of the initial horizontal stress and for the friction of the fault surfaces. It was found that the stress path during depletion is mainly controlled by the initial lateral stress ratio (LSR). The developed effective stresses with depletion are influenced by the fault geometry of the compartmentalized blocks. Plastic deformation develops for low LSR whereas for high values the system tends to remain in the elastic region. When plastic deformation takes place, it affects mainly the region near the fault. The reservoir deformation is dominated by vertical displacement which is higher near the fault region and nearly uniform in the remote area. The volumetric strain is dominated by compaction. More volatile conditions in relation to change of the friction coefficient and LSR were found for the normal fault geometry.